ANALISIS PENGARUH PERANAN INTERNAL AUDIT TERHADAP EFEKTIVITAS PROSEDUR PENAGIHAN PIUTANG USAHA PADA PT ADIRA DINAMIKA MULTI FINANCE - Lumentut, Lusiana; Ilat, Ventje; Pangemanan, Sifrid S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
PT Adira Dinamika Multi Finance is a company engaged in financial services. Thus, the collection of accounts receivable activity becomes an important part in the conduct of the company's revenue distribution was then used as working capital and asset turnover smoothness sustainable company. This study aims to determine, describe and explain the Influence of role Internal Audit Against Effectiveness Procedures Billing Accounts Receivable. The variables examined in this study is the role of Internal Audit ( X ) as the independent variable and Accounts Receivable Billing Procedures Effectiveness ( Y ) as the dependent variable . The method used is quantitative method then describe that aims to determine relationships or influence between variables through a quantitative approach and statistical tests. The results that has obtained of tests conducted of chi-square statistic is  9.56 where  hitung >   tabel ( 9.56 > 3.84 ) , which means there is a very strong influence between the two variables , with thus the hypothesis test results are acceptable , so it can be concluded that the role of internal audit affect the effectiveness procedures of the collection of accounts receivable .